Investigations on developing a key for identification of elite nutmeg tree - Vikram, H.C.; Mini Raj, N.; Krishnan, S. (Journal of Plantation Crops, 2017)
Nutmeg (Myristica fragrans Houtt.) is unique among tree spices, as the donor of two distinct spices; nutmeg and mace. Yield is a complex phenomenon in nutmeg. Fruit yield per tree is the targeted quantitative parameter which is dependent on several other yield related components. Hence, an attempt was made towards identification of an elite nutmeg tree using desirable characteristics which are easily measurable and recognizable. Forty six morphotypes of nutmeg selected from core collections in the Chalakudy river basin in Kerala in the age group of 15 years formed the material for study. These samples of nutmeg represented almost all nutmeg growing tracts of Kerala. The accessions were evaluated based on 51 qualitative and 38 quantitative characteristics and grouped based on similarities. Thirteen key quantitative characters were selected based on their impact on yield as well as commercial importance.The qualitative clusters were ranked based on relative best performance of the perceived key characters. Database was generated for the key characters and from this database, plausible value of each character was predicted. Accordingly, an elite nutmeg tree may be characterized as having the ideal characteristics with approximate values viz. tree height (8 m), canopy spread (E-W: 7 m, N-S: 8 m), number of flowers (6 per 10 cm2), fruit set percentage (37), number of fruits m-2 (19), fruit weight (81 g), thickness of pericarp (14 mm), dry mace weight (2 g), dry nut weight (10 g), kernel weight (7 g), ratio of nut to mace (6.6) and number of fruits per tree (3342). It is a simple key involving characters which are measurable and recognizable at the farmer level.